The effects of the COVID-19 pandemic on the diagnosis and prognosis of melanoma 2 years after the pandemic in two Romanian counties - Apostu, Adina Patricia; Vesa, Ștefan Cristian; Frățilă, Simona; Iancu, Gabriela; Bejinariu, Nona; Muntean, Maximilian; Șenilă, Simona C.; Baba, Oana Alexandra; Secășan, Cristina Pop; Ungureanu, Loredana (Frontiers in Medicine, 2024)
Background: The COVID-19 pandemic disrupted the healthcare system and negatively affected the diagnosis and management of melanoma worldwide. The purpose of this study is to investigate the long-term effects of the COVID-19 pandemic on the diagnosis and prognosis of melanoma. Material and Methods: This retrospective cohort study included histopathologically confirmed melanoma cases from March 2019 to February 2023 in Cluj and Bihor counties. Data from the post-COVID-19 period (March 2021 to February 2023) were compared to the pre-COVID-19 period (March 2019 to February 2020) and the COVID-19 period (March 2020 to February 2021). Patient characteristics, monthly diagnostics, histological subtypes, and key histological features were analyzed using statistical tests. Results: The number of melanoma cases diagnosed annually decreased by 31.37% and 23.75% in the first and second post-pandemic years, respectively, compared to pre-pandemic numbers. Diagnostic rates also decreased by 14.9% and 5.4% in the first and second post-pandemic years, respectively, compared to the pandemic period. Prognostic factors worsened in the post-pandemic period, with higher Breslow index and mitotic rate, and increased ulceration and thick melanomas compared to the pre-pandemic period. Conclusion: The COVID-19 pandemic had a long-lasting impact on the diagnosis of melanoma in Romania, resulting in advanced stages and unfavorable prognostic factors. Larger global studies are needed to comprehensively understand the pandemic's long-term effects on the diagnosis of melanoma.